2016
DOI: 10.1016/j.dld.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity and lymphoproliferation markers in naïve HCV-RNA positive patients without clinical evidences of autoimmune/lymphoproliferative disorders

Abstract: Published data concerning MC come mostly from symptomatic vasculitis. We analyzed HCV-patients without MC symptoms, founding cryoglobulins in the majority of them. The increased levels of FR-IgG and FLC in CGs-ANA-positive patients, suggest these test could be used to identify a state of silent autoimmune and/or lymphoproliferative condition before the transition to a frank disease in naïve HCV-patients without symptoms of extrahepatic manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…As reported in Table and visualized in Fig. , all HCV‐related MC (asymptomatic and symptomatic) patients displayed higher RF‐IgG mean levels than naïve; RF‐IgG can be considered a biomarker of a multiple‐stage disease, involving a clonal selection of antibodies due to chronic stimulus . Circulating auto‐antibodies are higher in patients with chronic HCV infection when compared to normal individuals and in presence of higher RF‐IgG levels it is conceivable that immune system is stimulated to a progressive activation, which in turn can trigger an autoimmune disorder.…”
Section: Discussionmentioning
confidence: 82%
“…As reported in Table and visualized in Fig. , all HCV‐related MC (asymptomatic and symptomatic) patients displayed higher RF‐IgG mean levels than naïve; RF‐IgG can be considered a biomarker of a multiple‐stage disease, involving a clonal selection of antibodies due to chronic stimulus . Circulating auto‐antibodies are higher in patients with chronic HCV infection when compared to normal individuals and in presence of higher RF‐IgG levels it is conceivable that immune system is stimulated to a progressive activation, which in turn can trigger an autoimmune disorder.…”
Section: Discussionmentioning
confidence: 82%
“…Together with the analysis of other markers, such as antinuclear antibodies (ANAs), the occurrence of the IgG3 subclass in the cryoprecipitate of HCV-positive patients was largely confirmed, and the switch of this specific subclass was evaluated on time [22] , [55] , [56] . The results showed that IgG3 in cryoprecipitates and ANA could indicate that the immune system is stimulated to a higher degree of activation and that this could represent a trigger factor in the long-term activation of the autoimmune mechanism.…”
Section: Introductionmentioning
confidence: 97%
“… CGs correlate with positive anti-ds DNA in SLE patients. [55] [55] [55] [56] [68] [69] Complement Involvement of complement in HCV manifestations, such as liver fibrosis and type II cryoglobulinemia. Reduced values of the C4 fraction of the complement can be observed in most patients with MC.…”
Section: Introductionmentioning
confidence: 99%
“… 1 7 Importantly, patients with advanced or pretransplant heart failure (HF) as defined by European Society of Cardiology (ESC) guidelines 8 are mostly unable to tolerate interferon (IFN)-based treatment regimes, resulting in very limited experience with this patient group regarding the possible pathogenic role of HCV infections. HCV infection often triggers disease in a broad spectrum of extrahepatic organs, 9 13 with innate immune and autoimmune pathogenic processes being involved, 14 16 and involvement of the myocardium in HCV-triggered autoimmunity would therefore not come as a surprise. There is no need to assume that HCV directly infects the myocardium, or that HCV impairs the function of a healthy heart and thus constitutes an independent cause of cardiomyopathy and HF.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that worldwide more than 70 million patients are chronically infected with HCV illustrates the possible clinical impact arising if cardiomyopathies were induced or aggravated by HCV. 14 , 17 If progressive HF or severe arrhythmias were induced in even a small fraction of all HCV-positive patients, this would still constitute a grave clinical problem. For this reason, it is most welcome that the long-standing hypothesis of cause-effect relationship between HCV infection and cardiac dysfunction may be conclusively tested now, enabled by the recent introduction of highly efficient and virus-specific direct-acting antiviral (DAA)-based anti-HCV regimens.…”
Section: Introductionmentioning
confidence: 99%